ABAcadabra: um aplicativo para o ensino de discriminações condicionais auditivo-visuais a indivíduos com transtorno do espectro do autismo - Guimarães, Luiza de Moura (Universidade Federal de São Carlos, 2018)
Autism Spectrum Disorder (ASD) is a developmental disorder that has deficits in social communication skills, and a high frequency of stereotypy and restricted behavior. Behavior Analysis is an important intervention that helps to decrease ASD symptoms. The ASD behavioral intervention involves, often, language development, since part of this population is no vocal. Spoken by others is a crucial repertoire that consists in learning relationships between stimuli. Many studies investigated that computer-based technologies to teach people with autism. In this context, Tables are a possible tool for teaching fundamental skills to ASD individuals, and it can help them to have a better quality of life. ABAcadabra can establish many skills can be teaching by the ABAcadabra, like conditional discrimination via MTS tasks. The present study proposed to (1) present a literature review that use tablet app to teach individuals with autism; (2) describe an evaluate tablet program called ABAcadabra, (2) test the use of app to grow receptive identification response; (3) evaluate three types of training: with ABAcadabra application alone, with paper alone, and combined form (ABAcadabra and paper tasks). In the review of studies that used tablet to teach individuals with ASD, was selected 30 articles, most of them used speech generate device to teach non vocal individuals; only two studies used MTS procedures to teach thru the app. In ABAcadabra description, in expert jugde’s evaluation, all judges agree that ABAcadabra is compatible with studies in Education and Behavior Analysis areas. Three experimental studies were conducted. In Experiment 1 with a non-vocal child diagnosed with ASD, training with paper was not enough to reach a teaching criterion for receptive identification of figures, and then combined training (with ABAcadabra and paper tasks) was conducted, and it was sufficient in the purchase (acquisition) of the discrimination repertoire. In Experiment 2, conducted with two children with ASD (one vocal and another non-vocal), a training to teach identifying photos of school colleagues by name was conducted. The experimental stimuli were separated into two groups, each one related to a type of training (with paper and with ABAcadabra). The results showed that the response was not stable when the task was present by ABAcadabra. In Experiments 3, the experimental stimuli were separated into three groups, each one related to the type of training (with ABAcadabra, paper and combined). One participant (ASD and non-vocal) had to identify items such as fruits and tools, and another (ASD and vocal) had to identify syllables. With both participants, combined training proved to be more efficient because it facilitated the rapid acquisition of responses, as well as the emergence of new responses. The ABAcadabra application may have much to contribute to teach symbolic relationships to children with autism.
ABAcadabra: an application to teach auditive-visual condicional discrimination to individuals with autism spectrum disorder
Keywords: Transtorno do Espectro do Autismo; Análise do Comportamento Aplicada; Discriminação condicional; Software ABAcadabra; Autism Spectrum Disorder; Applied Behavior Analysis; Conditional discrimination; MTS –matching-to-sample; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO